Estimates of the Population of the United States by Age, Sex, and Race 1980 to 1986 - Miller, Louisa; Bureau of the Census (DOC), Suitland, MD. Population Div. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The total population of the United States including the Armed Forces overseas was 241,596,000 on July 1, 1986. The median age of the population rose from 30.0 years on April 1, 1980, to 31.8 years on July 1, 1986, while the fastest growing segments of the population between 1980 and 1986 were the groups aged 35 to 44 years and 85 years and over. There were 2.3 million fewer children of school age and 2.3 million fewer young adults as the age groups which declined in growth were 5 to 13, 14 to 17, and 18 to 24. Estimates of the population from 1980 to 1986 are based on the 1980 census count, on an evaluation of the census count by demographic analysis, and on estimates of the components of population change from April 1, 1980 to July 1, 1986. The reported number of births and deaths was provided by the National Center for Health Statistics, U.S. Public Health Service. Data on members of the Armed Forces were obtained from the Department of Defense and from each branch of the military service. Estimates of net civilian immigration were derived by combining estimates for six separate categories. Tables showing the age structure of the population and the median age of the population are included. Charts illustrating the distribution of the total population, number of births by year and percent distribution of the white and black populations by age and sex are included. Detailed tables of total population, resident population,and civilian population from 1980 to 1986 are included in the report. (SM)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
Researchers.
Current Population Reports, Series P-25 n1000 Feb 1987.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Economics; Educational Resources; Ethnic Distribution; Instructional Materials; Migration; Population Distribution; Population Growth; Population Trends; Primary Sources; Social Studies; United States Government (Course); United States History; Population; Collected Works, Serials; Numerical/Quantitative Data